A DC-Link Ripple Current Reduction Method Based on Variable Switching Sequences for Three-Level NPC Inverters - Bae, Yun Jae; Lee, Kyo Beum (2023 IEEE Conference on Energy Conversion, CENCON 2023, 2023)
This paper presents a DC-link ripple current reduction method based on variable switching sequences for three-level neutral-point-clamped (NPC) inverters. Capacitors are used to maintain the stable DC-link voltage and current in the DC-link of a three-level NPC inverter. In addition, an allowable ripple current is a key factor affecting capacitor design. The ripple current in the DC-link increases the capacitor temperature and reduces lifespan, which can lead to decreased reliability of power conversion systems. The proposed method divides the voltage modulation region into two areas. An optimized switching scheme generates a new switching sequence by selecting the voltage vector that minimizes the DC-link current based on the voltage modulation region. The effectiveness of the proposed method is verified with simulation results.
Keywords: Dc-link; Neutral points; Neutral-point clamped inverters; Neutral-point current; Point currents; Ripple currents; Space vector pulse width modulation; Switching sequence; Three-level neutral point clamped; Three-level neutral-point-clamped inverte; DC-link; Neutral-point current; Space Vector Pulse-Width Modulation; Three-level NPC inverter